The Role of Social Support for Mother's Interest in Preventing Stunting - Ni Wayan Puspa Pandani (HM Publisher, 2020)
Stunting is a condition where the child's height is too low. Indonesia is ranked fifth in the world of stunting. Stunting is the result of a complex interaction of family, environment, socioeconomic, and culture including behavior related to interest in preventing stunting. Social Support is an interpersonal transaction that is shown by providing assistance to others. This study was conducted to determine the effect of social support role for mother interest in preventing stunting using primary data through focus group discussion and Depth Interview on pregnant mothers and mothers who have children ≤2 years.Used the concept of The Pland Behavior Theory as the basic theory of this study. The study was conducted in June 2017-July 2017 in several urban villages in Palembang. From seven informants conducted by Depth Interview, various proportion of social support received by informants.Overall social support plays a role in determining the interest of mothers to preventing stunting, All mothers are very interested in preventing stunting.The greatest influence in determining the mother's interest to prevent stunting is Behavioral Control aspect in terms of Perceived Power that is the sense and the emotional bond that the child is the most important part of a mother and the sense of not wanting the child to have a stunting growth disorder.